KONTRIBUSI KEBIASAAN BEROLAHRAGA DENGAN KEMAMPUAN GERAK DASAR SISWA KELAS V SEKOLAH DASAR (STUDI PADA SD NEGERI PUCANG I SIDOARJO) - NORMADIAN SANTOSO, DANDIK (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract The objectives subjects of sports education are to improve the physical potential, cultivate the sportivity, and civilize healthy living. In improving physical potential are the goal of improving basic movement skills and abilities of students. To achieve these objectives the students with the help of the teacher should be able to absorb the knowledge of the sport given by the teacher through motor learning. In addition, students should be able to get used to exercising outside lesson hours sport. Accustomed to exercising with the students naturally learn motion. Because the core of the sport is a motion. The more often students do exercise they will get a lot of motion experience so their motor ability and motor skills can be improved. The purpose of this study was to determine the contribution of their exercise habits with the basic motor ability of fifth grade students of Pucang I Sidoarjo Elementary School, and to determine the contribution of sport habits with  the basic motor ability of fifth grade students of Pucang I Sidoarjo Elementary School. The type of this research is non-experimental research through quantitative approach with a correlational design. The population in this research were all fifth grade students of Pucang I Sidoarjo Elementary School, amounting to 116 students. While the sampling technique used cluster random sampling with a sample of 37 students, while the students who had the test amounted only 33 students, because 4 other students who could not participate is illness. The instrument in this research was a questionnaire to measure students sport habits, and the carpenter motor ability tests to measure students basic motor ability. Data analysis that applied is Spearman correlation. Based on the data  analysis found that the variable sport habits with basic motor abilitys have rhitung result of 0.522, α 0.05 with P value 0.002. This indicates that the P value 0.002 ≤ α 0.05  , which means that H0 is rejected and Ha accepted. Has a determination coefficient as big as 27.25%. Thus it can be concluded that there is a significant correlation between sport habits with the basic motor ability of fifth grade students of Pucang I Sidoarjo Elementary School with ties at 27, 25%. Keywords: Sport Habits, Basic Motor Ability.